Preferensi Masyarakat Terhadap Produk Gadai di Pegadaian Syariah (Studi Kasus Unit Gadai Emas Cabang Kota Pinang) - Muliani Putri (Universitas Muhammadiyah Enrekang, 2022)
Diversification of Islamic pegadaianing products as a form of service to encourage customer preferences for Islamic pegadaianing, one of which is the gold pawn product. This makes product marketing strategy the most important part, and an important stage of marketing is analyzing customer behavior. On this basis, this study focuses on the factors that influence the preference of pawning gold customers of the Pinang Branch Gold Pawn Unit. By testing and analyzing 5 (five) factors that are believed to influence the preferences of Gadai Emas customers, namely belief, religion, profit, service and promotion. This research is a field study using a qualitative approach, based on primary and secondary data from observations and interviews with pegadaian management, using a simple purposeful sampling method. The data analysis technique used is frequency analysis, which is to test the level of validity and reliability of the questionnaire data. The answer to this research problem was found, namely five factors of preference for gold pawning customers have an influence in pawning gold at the Pinang City Pawn Gold Branch Unit, the factors sequentially are as follows: religious and trust with high scores then profit, service, and promotion.